EXPLORING GENDERED LANGUAGE USE: MULTILINGUAL FEMALE ADOLESCENTS IN BANDUNG, INDONESIA - Ida Zuraida Supri; Tajudin Nur; Susi Yuliawati; Rosaria Mita Amalia (University of Kuningan, 2023)
This study focuses on the language characteristics of multilingual female teenagers in Bandung, a city with a diverse ethnic population. The research is based on a small sample of 16-18 year old students from a private high school and uses a descriptive-analytic method to analyze recorded conversations as primary data and interviews as secondary data. The study categorizes and analyzes the language variations and characteristics of the teens' speech, using theories from Lakoff (2017) and Holmes (2022). The results suggest that some, but not all, of the language features proposed by Lakoff are present in the teens' speech. Additionally, the study identifies six language functions used, including lexical hedges, tagging questions, empty adjectives, reinforcers, emphasis stress, and rising intonation. Due to the participants' multilingualism, the conversations often involve a mix of Indonesian, local (Sundanese), and English codes.